2013
DOI: 10.1016/j.dsi.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous cryptococcosis in an immunocompetent man: A case report

Abstract: a b s t r a c tCutaneous cryptococcosis usually develops secondary to hematogenous spread in immunocompromised hosts. Primary cutaneous cryptococcosis (PCC) is a rare condition characterized by localized skin eruptions and positive culture for Cryptococcus neoformans but without dissemination to the internal organs. Herein, we describe a typical case of PCC in an immunocompetent male who presented with a 1-month history of scattered erythematous indurated papules and plaques on his arm and without fever. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…PCC is a rare condition that is distinct from secondary cutaneous infections developing after infection of other organs. 5 ) The diagnostic criteria of PCC are confined to the skin and the condition can be diagnosed without clinical evidence of systemic involvement during follow-up for at least 4 weeks after confirmation of C. neoformans infection through skin biopsy or culture. 1 ) Neuville et al 2 ) also reported diagnostic characteristics of PCC, which included rural residency, susceptible environment for trauma, localized lesions, no systemic symptoms, and no antigen detection.…”
Section: Discussionmentioning
confidence: 99%
“…PCC is a rare condition that is distinct from secondary cutaneous infections developing after infection of other organs. 5 ) The diagnostic criteria of PCC are confined to the skin and the condition can be diagnosed without clinical evidence of systemic involvement during follow-up for at least 4 weeks after confirmation of C. neoformans infection through skin biopsy or culture. 1 ) Neuville et al 2 ) also reported diagnostic characteristics of PCC, which included rural residency, susceptible environment for trauma, localized lesions, no systemic symptoms, and no antigen detection.…”
Section: Discussionmentioning
confidence: 99%